2020
DOI: 10.1074/jbc.ra120.012522
|View full text |Cite
|
Sign up to set email alerts
|

Adipose mesenchymal stem cell-derived extracellular vesicles containing microRNA-26a-5p target TLR4 and protect against diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is a complication of diabetes that is increasing in prevalence in China. Extracellular vesicles (EVs) carrying microRNAs (miRs) may represent a useful tool in the development of therapies for DN. Here, we report that EVs released by adipose-derived mesenchymal stem cells (ADSCs) during DN contain a microRNA (miR), miR-26a-5p, that suppresses DN. Using bioinformatic analyses, we identified differentially expressed miRs in EVs from ADSCs and in DN and predicted downstream regulatory tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 45 publications
(44 reference statements)
3
59
0
Order By: Relevance
“…Duan et al revealed that the Exo isolated from the conditioned medium of human urine-derived stem cells inhibits the expression of VEGFA and the apoptosis of podocytes by miRNA-16-5p, thereby relieving DN [83]. It is proven by Duan et al that ADSC-EV miRNA-26a-5p suppresses the hyperglycaemiainduced apoptosis of podocytes in mice by downregulating the TLR4 and NF-κB/VEGFA signalling pathways [84]. Anti-fibrosis is also a major mechanism invoked in DN treatment with MSC-EVs.…”
Section: Msc-evs and Dnmentioning
confidence: 99%
“…Duan et al revealed that the Exo isolated from the conditioned medium of human urine-derived stem cells inhibits the expression of VEGFA and the apoptosis of podocytes by miRNA-16-5p, thereby relieving DN [83]. It is proven by Duan et al that ADSC-EV miRNA-26a-5p suppresses the hyperglycaemiainduced apoptosis of podocytes in mice by downregulating the TLR4 and NF-κB/VEGFA signalling pathways [84]. Anti-fibrosis is also a major mechanism invoked in DN treatment with MSC-EVs.…”
Section: Msc-evs and Dnmentioning
confidence: 99%
“…Wu et al 19 suggested that miR-100-5p-abundant MSC-exos attenuated cartilage injury via inhibition of mammalian target of rapamycin in osteoarthritis. Duan et al 20 found that adipose mesenchymal stem cell-derived EVs containing miR-26a-5p protected against diabetic nephropathy. In addition, depletion of miRNAs from EVs significantly weakened their regenerative potential in glycerol-induced AKI, suggesting the vital role of miRNA in the therapeutic effect of MSC-EVs 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The interest in AT-MSC-EVs has increasingly grown, due to the wide range of AT sources and their relatively easy accessibility [9]. AT-MSC-EVs have been isolated not only from human cells, but also from mouse [24][25][26][27][28][29][30][31][32], rat [33,34], pig [35][36][37][38], and rabbit [39,40] cells. The main objective of most published studies on AT-MSC-EVs was to evaluate their potential use as a new therapeutic approach to treat various diseases.…”
Section: Introductionmentioning
confidence: 99%